Good character: the implications of personality development and psychopathology for citizenship - Stephen Attard; Solange Valdez-Symonds; Steve Valdez-Symonds; Andrew Iles; Frances Maclennan (BJPsych Bulletin)
The introduction of new legislation in 2006 brought about changes to the way citizenship applications were considered in the UK. Over the intervening years, several hundred children born in the UK have been denied British citizenship as a result of changes to the ‘good character’ requirement in the legislation – namely its extension to cover all those aged 10 years or older applying for citizenship, including individuals who were born in the UK. As a result of the formulaic way in which this requirement is assessed, citizenship can be denied on the basis of historical patterns of behaviour or offending from childhood. This article will consider whether the current approach to assessment of character in the context of applications for British citizenship is meaningful or appropriate, given developments in our understanding of normative psychological and neurological development and also the impact of psychosocial adversity, trauma, and broader psychopathological or neurodevelopmental conditions.